DOP06 Dynamic shifts in the balance of gut homing Treg and Th17 cells play a critical role in ulcerative colitis and may predict response to vedolizumab therapy. (25th January 2019) - Hermangild Kottoor, S; Kassam, Z; Pavlidis, P; Alberts, E; Ibraheim, H; Constable, L; Digby-Bell, J; Warren, D; Odukwe, S; Samaan, M; Irving, P; Sanderson, J; et al.
Abstract: Background: The balance between regulatory T cells (Treg) and Th17 cells is thought to play a key role in the development and outcomes of human autoimmune and inflammatory diseases. Therapeutic targeting of gut trafficking lymphocytes using vedolizumab, an anti-integrin monoclonal antibody, is an effective treatment for IBD. However, little is known about the effect of vedolizumab on different effector T-cell subsets or Tregs. We analysed the profile of circulating gut homing effector memory T-cell subsets and Tregs as well as the Treg/Th17 immune balance in ulcerative colitis (UC) patients. We also evaluated the longitudinal impact of vedolizumab on a small cohort of prospectively recruited patients. Methods: Using multi-parametric flow cytometry, we analysed the gut homing (β7+) effector T cells (CD4+CD45RA-CD45RO+CCR7-) and their functional lineages (Th1, Th2, and Th17) based on chemokine receptor expression (CXCR3, CCR4, and CCR6, respectively) as well as memory Treg (CD4+CD25+CD127-CD45RA-CCR4+) from peripheral blood of healthy controls (HC) and UC patients. Peripheral blood was taken from patients before their first dose of vedolizumab and at each subsequent infusion. Results: The ratio of gut homing Treg to Th17 cells was significantly lower in UC ( n = 21) compared with HC (1.4 in HC vs. 0.5 in UC, p = 0.01). Although there was minimal impact on gut homing Th1 and Th2 cells in vedolizumab treated ( n = 15) patients (comparison between baseline [BL] and Week 14), both gut homing Th17 and Treg compartments increased over the same time period (from 17.3% at BL to 45.3% at Week 14 for Th17 and from 9.7% to 57.2% for Treg). Intriguingly, while comparing clinical response to vedolizumab (30% fall in SCCAI at Week 14 compared with BL), preliminary data indicated that the magnitude of increase in gut homing Tregs at Week 2 is much higher in responders compared with non-responders (3-fold increase in responders vs. −0.4-fold increase in non-responders). This increase was more prominent in the gut homing Treg/Th17 ratio in responders at Week 2 (6-fold increase in responders vs. −0.7-fold increase in non-responders, p = 0.02) and could distinguish between the two groups, thereby increasing the positive probability of response to 80%. Conclusions: UC is characterised by a shift in the proportional abundance of Treg and TH17 cells, implicating a disruption of Treg/Th17 immune balance. The magnitude of increase in the gut homing Treg/Th17 ratio following vedolizumab therapy could differentiate between responders and non-responders to treatment as early as at Week 2 (following the first dose of vedolizumab infusion), raising the possibility that this test could be used as an early biomarker to aid decision-making in clinical practice.